CO2 recovery process for supercritical extraction - D'ORAZIO, ROBERT; LEITCH, KELLY; HARTIGAN, GAVIN (2004)
Carbon dioxide recovery process for supercritical extraction involves providing a process stream from a supercritical extraction procedure, reducing the pressure of the process stream below critical pressure, venting carbon dioxide vapor to exhaust, cooling the process stream, separating the two phase mixture into a process liquid, passing filtered process vapor phase stream through an adsorber, and drying purified carbon dioxide vapor stream. Carbon dioxide recovery process for supercritical extraction comprises providing a process stream (61) including pressurized carbon dioxide, extraction process waste, and optionally at least one co-solvent, from a supercritical extraction procedure (60); reducing the pressure of the process stream below critical pressure; venting low pressure carbon dioxide vapor (66) to exhaust; cooling the process stream to form a two phase mixture; separating the two phase mixture into a process liquid (71), containing co-solvent and a process vapor phase stream (72); collecting the process liquid; filtering the process vapor phase stream to remove particulates and optionally residual co-solvent; passing the filtered process vapor stream (81) through an adsorber (85) to remove trace impurities to form a purified carbon dioxide vapor stream; and drying the purified carbon dioxide vapor stream (90) to remove residual water vapor. An independent claim is also included for an apparatus for the recovery of carbon dioxide from a supercritical extraction process, which comprises mechanisms for reducing the pressure of the carbon dioxide, a vent for passing low pressure carbon dioxide vapor resulting from the pressure reduction to exhaust, a separator for forming the process stream into two phases comprising a process liquid, a container for collecting the process liquid, at least one filter to remove particulates and optionally residual co-solvent from the process vapor phase stream, an adsorber to remove trace impurities from the filtered process vapor stream to form a purified carbon dioxide vapor stream, at least one dryer to remove residual water vapor from the purified carbon dioxide vapor stream, and a flow network having conduits connecting the components of the apparatus and including a connection between the dryer and a condenser associated with a supply of carbon dioxide to the extraction process. The flow network has valves associated with the conduits to allow for isolation of components of the apparatus. A carbon dioxide recovery apparatus (1) and process for supercritical extraction includes providing a process stream (61) from a supercritical extraction procedure (60) in which the process stream (61) includes pressurized carbon dioxide, extraction process waste and optionally at least one co-solvent; reducing the pressure of the process stream below critical pressure; venting low pressure carbon dioxide vapor (66) to exhaust; cooling the process stream to form a two phase mixture; separating the two phase mixture into a process liquid (71), containing co-solvent if present, and a process vapor phase stream (72); collecting the process liquid; filtering the process vapor phase stream (72) to remove particulates and optionally residual co-solvent; passing the filtered process vapor stream (81) through an adsorber (85) to remove trace impurities to form a purified carbon dioxide vapor stream (90); and, drying the purified carbon dioxide vapor stream (90) to remove residual water vapor.